Criteria for customer agglomeration for a new footwear retail: a case study of a regional footwear brand in India. (1st January 2014) - Mukherjee, Srabanti; Das, Prasun
A well-known regional footwear chain in India during its expansion wanted to identify the key parameters to ensure customer agglomeration in its new retails. Based on the survey data of the customers of existing retails of the said footwear chain, we have tested the association amongst the demographic attributes and a significant association amongst income and store selection and also residential location and store selection was observed. Finally, we have resorted to signal-to-noise ratio metrics to find out the relative importance of the attributes in terms of buyer's perception. Our study indicates that given the stores are going to be opened in hitherto untapped locations, therefore, rather than trust and patronage, focussing on the hedonic and utilitarian aspects of the concerned footwear retails may ensure customer agglomeration in new stores in the short run.